The nature of scientific/technical texts from viewpoint of translation studies - Mastná, Eva (Tomas Bata University in Zlín, 2010)
The aim of the bachelor's thesis is to undergo a deep survey of the nature of scientific and technical text. The thesis consists of two main parts, theory and analysis. The theory deals with introducing contemporary classification of styles, and mainly to describe scientific, technical and legal style from the viewpoint of translation studies. The purpose of the theory is to provide a reader with the aspects of chosen styles that a translator must consider and main principles he/she must follow when translating from English into Czech and vice versa. Analysis fulfills the main objective of the thesis, to support given knowledge about the scientific and technical translation and to find common feature among selected substyles represented by excerpts of texts from the fields of economics, law, physics, and chemistry.